Procedural tactics in the investigation of property damage to a law enforcement officer - A. P. Chyzh (Law and Safety)
One of the structural components of the forensic methodology for investigating intentional destruction or damage to property of a law enforcement officer is the specific tactics of certain investigative (detective) actions. The complexity of their conduct, as well as their significant effectiveness in collecting evidence of a person's guilt and in clarifying the circumstances of the said criminal offence, necessitate a thorough study on this issue. Considering this, the purpose of the study is to determine the tactical and organisational features of investigative (detective) actions during the investigation of intentional destruction or damage to property of a law enforcement officer.